Nucleotide Second Messenger‐Mediated Regulation of a Muralytic Enzyme in Streptomyces - St‐Onge, Renée J.; Haiser, Henry J.; Yousef, Mary R.; Sherwood, Emma; Tschowri, Natalia; Al‐Bassam, Mahmoud; Elliot, Marie A. (Molecular microbiology, 2015)
Summary Peptidoglycan degradative enzymes have important roles at many stages during the bacterial life cycle, and it is critical that these enzymes be stringently regulated to avoid compromising the integrity of the cell wall. How this regulation is exerted is of considerable interest: promoter‐based control and protein‐protein interactions are known to be employed; however, other regulatory mechanisms are almost certainly involved. In the actinobacteria, a class of muralytic enzymes – the ‘resuscitation‐promoting factors’ (Rpfs) – orchestrates the resuscitation of dormant cells. In this study, we have taken a holistic approach to exploring the mechanisms governing RpfA function using the model bacterium Streptomyces coelicolor and have uncovered unprecedented multilevel regulation that is coordinated by three second messengers. Our studies show that RpfA is subject to transcriptional control by the cyclic AMP receptor protein, riboswitch‐mediated transcription attenuation in response to cyclic di‐AMP, and growth stage‐dependent proteolysis in response to ppGpp accumulation. Furthermore, our results suggest that these control mechanisms are likely applicable to cell wall lytic enzymes in other bacteria. Streptomyces bacteria have an unusual life cycle, which culminates in the development of dormant spores. Spore germination and outgrowth require the activity of dedicated cell wall‐degrading enzymes, the regulation of which is poorly understood. Here, we have uncovered an intricate, multi‐level regulatory network orchestrated by three different signaling molecules.